Involvement of ς(S) in Starvation-Induced Transposition of Pseudomonas putida Transposon Tn4652 - Ilves, Heili (American Society for Microbiology, 2001)
Transpositional activity of mobile elements can be induced by different environmental stresses. Here, we present evidence that transposition of Tn4652 is elevated in stationary-phase Pseudomonas putida and suppressed in an isogenic ς(S)-defective strain. We demonstrate that transcription from the Tn4652 transposase promoter is controlled by the stationary-phase-specific sigma factor ς(S). To our knowledge, this is the first example of direct stationary-phase-specific regulation of a mobile element transposase. Data presented in this report support the idea that activation of transposition under stressful conditions could be an inducible process.